2012
DOI: 10.1111/hepr.12029
|View full text |Cite
|
Sign up to set email alerts
|

Perihepatic lymph node enlargement observed at a general health examination: A cross‐sectional study

Abstract: The incidence of PLNE in the general population may vary with the prevalence of chronic liver disease, especially HCV infection. When PLNE is observed, liver disorders should be first surveyed including HCV infection even with normal serum alanine aminotransferase levels. PLNE with para-aortic lymph node enlargement may be suggestive of a malignant lesion. The incidence of PLNE of unknown etiology may be approximately 1% in the general population, which may be just followed up without further change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Thus, PLNE may be observed in as much as 10% of patients with chronic HBV infections. Then, we compared the frequency of PLNE in subjects with different backgrounds; in our previous studies, PLNE was detected in 20.0% (169/846) of patients with CHC and in 1.6% (69/4234) of subjects who underwent a general health examination . As shown in Figure , the frequency of PLNE in patients with chronic HBV infection was significantly higher than that in subjects undertaking a general health examination ( P < 0.0001) but lower than that in CHC patients ( P < 0.0001).…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Thus, PLNE may be observed in as much as 10% of patients with chronic HBV infections. Then, we compared the frequency of PLNE in subjects with different backgrounds; in our previous studies, PLNE was detected in 20.0% (169/846) of patients with CHC and in 1.6% (69/4234) of subjects who underwent a general health examination . As shown in Figure , the frequency of PLNE in patients with chronic HBV infection was significantly higher than that in subjects undertaking a general health examination ( P < 0.0001) but lower than that in CHC patients ( P < 0.0001).…”
Section: Resultsmentioning
confidence: 87%
“…We examined the association between PLNE and clinical findings such as liver fibrosis, hepatocellular injury or the presence of HCC in patients with chronic HBV infection (the primary end‐point of this study). We previously reported the prevalence of PLNE in the patients with CHC or the patients underwent general health examinations (general population) . Using the results of our previous studies, we then compared the prevalence of PLNE in the patients with chronic HBV infection to patients with CHC or general population (the secondary end‐point).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 -24 Lymph nodes of lymphatic circulation system in liver are well known to exist in the porta hepatis area, and inflammatory processes in organs frequently give rise to hyperplasia of regional lymph nodes. 25 As described in detail previously, 6 Dietrich et al had investigated the volume of enlarged lymph nodes within the hepatoduodenal ligament among HCV patients, and concluded that PLNE is a predictive factor for the presence of severe inflammatory activity. In their study, the mean perihepatic lymph node volume in healthy controls was lower than in HCV-infected patients (2.2±1.8 ml versus 16.0±13.2 ml; p<10 −6 ).…”
Section: Discussionmentioning
confidence: 88%